Bacterial infections associated with allogenic bone transplantation - Stepanović, Željko Lj.; Ristić, Branko M. (Vojnosanitetski pregled, 2015)
Background/Aim. Bone allografts are frequently used in orthopedic reconstructive procedures carrying a high risk for recipients. To assess the nature and frequency of allograft contamination and associated surgical infection the case records from our institutional bone bank were reviewed. Methods. We retrospectively analyzed the microbiology of discarded bone allografts and the surgical site of the recipients. A case series of patients who acquired surgical site infection after allogenic bone transplantation was presented. Swab culturing was conducted on 309 femoral heads from living donors who underwent partial and total hip arthroplasty between January 2007 and December 2013. To prevent potential bone allograft contamination we used saline solution of 2.0 mg/ml of amikacin during thawing. The overall infection rate was analyzed in 197 recipients. Results. Of the 309 donated femoral heads, 37 were discarded due to bacterial contamination, giving the overall contamination rate of 11.97%. The postoperative survey of 213 bone allotransplantations among 197 recipients showed the infection rate of 2.03%. The coagulase-negative Staphylococcus was the most commonly identified contaminant of bone allografts and recipient surgical sites. Conclusion. The allograft contamination rate and the infection rate among recipients in our institution are in accordance with the international standards. The coagulase-negative Staphylococcus was the most commonly identified contaminant of bone allografts and recipient surgical sites. There is no strong evidence that surgical site infections were associated with bone allograft utilization. We plan further improvements in allograft handling and decontamination with highly concentrated antibiotic solutions in order to reduce infection risk for recipients.